A Civil Society Deferred : The tertiary grip of violence in the Sudan - Gallab, Abdullahi A. (University Press of Florida, 2011)
The sociopolitical construction of a country -- Constructing new identities -- The malignant tumor of the colonial state : the antibodies -- A tale of three cities : Khartoum -- A tale of three cities : Omdurman -- A tale of three cities : Cairo -- The creation of the center -- The creation of the margin. LC Subjects Violence--Sudan. Sudan--Politics and government.
English
Keywords: HM(1)-1281 Sociology; Sudan